MENGEMBANGKAN KEMAMPUAN BAHASA DAN MOTIVASI BELAJAR PADA ANAK KELOMPOK A MENGGUNAKAN MODEL AKTIF - Mahriani, Ariska; Jannah, Fathul (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The problem in this study is the low language skills and learning motivation of group A children at Mukhlisoh Barito Kuala Kindergarten. This is caused by the low language skills of children which are not yet optimal, the lack of active involvement of children in learning activities so that children's motivation to learn is low when children carry out learning activities, so that they are always not enthusiastic and do not complete their assignments. The purpose of this study was to describe teacher activities, analyze children's activities, analyze the increase in children's learning motivation, and analyze the results of children's language development. The research approach used qualitative and quantitative with the type of classroom action research (PTK) which was carried out in 4 meetings. The subjects of this study were group A children at Mukhlisoh Barito Kuala Kindergarten, totaling 26 children, including 15 boys and 11 girls. The results of this study indicate that the teacher's activity at meeting 1 obtained a score of 16